Colonization is Misogynistic: The Sterilization of Native American Women in the Twentieth Century - Arguelles, Mandeline (The Toro Historical Review, 2024)
This paper is a historical essay based on the collection of research from several scholars, such as Juliana Barr, Sarah Deer, and Nancy Shoemaker, on the continuous cycle of colonial violence against the indigenous people of North America. Colonial violence used the matriachal system of traditional native society, which valued women as the center of their communities, to target native women due to their patriarchal values. This paper investigates the destruction of traditional native society as central to colonization, beginning with European contact and it's continuous cycle within contemporary society. It focuses on the forced sterilization of Native American women in the 1960s and 1970s in the United States, to demonstrate that colonial violence is not an issue of the past.